Wolbachia causes cytoplasmic incompatibility but not male‐killing in a grain pest beetle. Issue 24 (24th October 2022) - Kiefer, Julian S. T.; Schmidt, Gerrit; Krüsemer, Ronja; Kaltenpoth, Martin; Engl, Tobias
Abstract: The endosymbiotic Wolbachia is one of the most common intracellular bacteria known in arthropods and nematodes. Its ability for reproductive manipulation can cause unequal inheritance to male and female offspring, allowing the manipulator to spread, but potentially also impact the evolutionary dynamics of infected hosts. Estimated to be present in up to 66% of insect species, little is known about the phenotypic impact of Wolbachia within the order Coleoptera. Here, we describe the reproductive manipulation by the Wolbachia strain w Sur harboured by the sawtoothed grain beetle Oryzaephilus surinamensis (Coleoptera, Silvanidae), through a combination of genomics approaches and bioassays. The Wolbachia strain w Sur belongs to supergroup B that contains well‐described reproductive manipulators of insects and encodes a pair of cytoplasmic incompatibility factor ( cif ) genes, as well as multiple homologues of the WO‐mediated killing ( wmk ) gene. A phylogenetic comparison with wmk homologues of w Mel of Drosophila melanogaster identified 18 wmk copies in w Sur, including one that is closely related to the w Mel male‐killing homologue. However, further analysis of this particular wmk gene revealed an eight‐nucleotide deletion leading to a stop‐codon and subsequent reading frame shift midsequence, probably rendering it nonfunctional. Concordantly, utilizing a Wolbachia ‐deprived O. surinamensis population and controlled mating pairs of w Sur‐infected and noninfected partners, we found no experimental evidence for male‐killing. However, a significant ~50% reduction of hatching rates in hybrid crosses of uninfected females with infected males indicates that w Sur is causing cytoplasmic incompatibility. Thus, Wolbachia also represents an important determinant of host fitness in Coleoptera.